A new error estimation approach based on fuzzy logic system for H-R adaptive boundary element method - Chen, Yiming; Zhou, Zhiquan; Zhang, Jing; Li, Yulian; Wang, Xiaojuan (Applied mathematics and computation, 2011)
Conventional adaptive boundary element method cannot be universally applied to solve many more problems than the subject it discussed, and different error estimation formulas need to be designed for varied problems. This paper put forward a new error analysis method based on the fuzzy logic system, which is able to make error estimation effectively using human expert experience, and solve the two classical elasticity problems in conjunction with the H-R adaptive boundary element method. Numerical examples have illustrated the effectiveness, superiority and potential of a fuzzy logic approach in the adaptive boundary element method.